1.3 Fermat's and Euler's Theorem: * Fermat's Theorem : For any field, the nonzero elements form a group under the field multiplication. In particular, for β€π , the elements 1, 2, 3, … , π − 1 form group of order π − 1 under multiplication modulo π. Theorem 3.1: (Little Theorem of Fermat): If π ∈ β€ and π is a prime not dividing π, then π divides ππ−1 − 1 , that is, ππ−1 ≡ 1 (πππ π) for π β’ 0 (πππ π) . Corollary 3.2: If π ∈ β€ , then ππ ≡ π (πππ π) for any prime π. Proof: Follows from Theorem 3.1 if π β’ 0 (πππ π) . If π ≡ 0 (πππ π), then both side reduce to 0 ππππ’ππ π. Example: Compute the remainder of ππππ when divided by 13 using Fermat's Theorem. 8103 ≡ (812 )8 (87 ) ≡ (18 )(87 ) ≡ 87 ≡ (−5)7 ≡ (25)3 (−5) ≡ (−1)3 (−5) ≡ 5 (πππ 13) . * Euler's Generalization : Theorem 3.3: The set πΊπ of nonzero elements of β€π that are not 0 divisors forms a group under multiplications modulo π. Proof: First we must show that πΊπ is closed under multiplication modulo π. Let π, π ∈ πΊπ . If ππ ∉ πΊπ , then there would exists π ≠ 0 in β€π such that (ππ)π = 0 . So (ππ)π = 0 implies that π(ππ) = 0 . Since π ∈ πΊπ 1 and π ≠ 0 , we have ππ ≠ 0 by definition of πΊπ . But then π(ππ) = 0 would imply that π ∉ πΊπ contrary to assumption. We now show that πΊπ is a group. Multiplication modulo π is associative, and 1 ∈ πΊπ . It remains to show that for π ∈ πΊπ , there is π ∈ πΊπ such that ππ = 1. Let 1, π1 , … , ππ be the elements of πΊπ . The elements π1, π π1 , … , πππ are all different, for if πππ = πππ , then π(ππ − ππ ) = 0, and since π ∈ πΊπ and thus is not a divisor of 0, we must have ππ − ππ = 0 . Therefore, by counting, we find that either π1 = 1, or some πππ must be 1, so π has a multiplicative inverse. Definition: Let π be a positive integer. π(π) is the number of positive integers less than or equal to π and relatively prime to π. Note that π(1) = 1. Example: Let π = 12. The positive integers less than or equal to 12 and relatively prime to 12 are 1, 5, 7, and 11. So π(12) = 4. Note: By the definition of the characteristic of a ring, π(π) is the number of nonzero elements of β€π that are not divisors of 0. This function π: β€+ βΆ β€+ is the Euler phi-function. Theorem 3.4: ( Euler's Theorem): If π is an integer relatively prime to π, then ππ(π) − 1 is divisible by π, that is, ππ(π) ≡ 1 (πππ π). Proof: If π is relatively prime to π, then the coset π + πβ€ of πβ€ containing π contains an integer π < π and relatively prime to π. As the multiplication of these cosets by multiplication modulo π of representatives is well-defined, we have 2 ππ(π) ≡ π π(π) (πππ π). But by Theorem 2.1 and Theorem 3.3, π can be viewed as an element of the multiplication group πΊπ of order π(π) consisting of the π(π) elements of β€π relatively prime to π. Thus, π π(π) ≡ 1 (πππ π) and our theorem follow. Example: Compute ππ (πππ ππ) using Euler's Theorem. Let π = 12. From the previous example, we have π(12) = 4. Thus, for any integer relatively prime to 12, we have π4 ≡ 1 (πππ 12). For example, with π = 7, we have 74 = (49)2 = 2,401 = 12(200) + 1 So, 74 ≡ 1 (πππ 12). The easy way to compute 74 (πππ 12) without using Euler's Theorem is to compute it in β€12 . In β€12 , we have 7=-5 so (74 ) = (72 )2 = ((−5)2 )2 = (25)2 = (1)2 = 1 . 3 1.4 The Field of Quotients of an Integral Domain: * The Construction: The steps we need to enlarge an integral domain π· to a field of quotients πΉ are as follow: 1. Define what the elements of πΉ are to be. 2. Define the binary operations of addition and multiplication on πΉ. 3. Check all the field axioms to show that πΉ is a field under these operations. 4. Show that πΉ can be viewed as containing π· as an integral subdomain. Step 1: Let π· be an integral domain, and form the Cartesian product π· × π· = {(π, π)⁄ π , π ∈ π·}. The ordered pair (π, π) is representing a formal quotient π⁄π . So, if π· = 2 β€ , the pair (2, 3) represent the number . The pair (2, 0) represent no 3 element of β . Thus we need to cut the set π· × π· down. Let π be the subset of π· × π· given by π = {(π, π)⁄π , π ∈ π·, π ≠ 0}. Now π is still not going to be a field because, with π· = β€ , different pairs of integers such as (2, 3) and (4, 6) can represent the same rational number. So, we will define when two elements of π represent the same element of πΉ, that is, when two elements of π are equivalent. Definition: Two elements (π, π) and (π, π) in π are equivalent, denoted by (π, π)~(π, π) iff ππ = ππ . Lemma 4.1: The relation between elements of the set π as just described is an equivalence relation. Proof: We need to check the three properties of an equivalence relation. 4 Reflexive. (π, π)~(π, π) since ππ = ππ , for multiplication in π· is commutative. Symmetric. If (π, π)~(π, π) , then ππ = ππ . Since multiplication in π· is commutative, thus ππ = ππ . Therefore, (π, π) = (π, π) . Transitive. If (π, π)~(π, π) and (π, π)~(π, π ), then ππ = ππ and ππ = ππ. As π ≠ 0 and π· is an integral domain, so the cancellation laws hold. Thus, ππππ = ππππ and so ππ = ππ. So (π, π)~(π, π ) . Notation: ~ gives a partition of π into equivalence classes. So let [(π, π)] be the equivalence class of (π, π) in π under the relation ~ . Step 1 is finished by defining πΉ to be the set of all equivalence classes [(π, π)] for (π, π) ∈ π . Step 2: We need the following lemma to define addition and multiplication in πΉ. Note that if π· = β€ and [(π, π)] is viewed as (π⁄π) ∈ β , these definition applied to β give the usual operation. Lemma 4.2: For [(π, π)] and [(π, π)] in , the equations [(π, π)] + [(π, π)] = [(ππ + ππ, ππ)] and [(π, π)][(π, π)] = [(ππ, ππ)] give well-defined operations of addition and multiplication on πΉ . Proof: If [(π, π)] , [(π, π)] ∈ πΉ , then (π, π), (π, π) ∈ π . So π ≠ 0 and ≠ 0 . As π· is an integral domain, ππ ≠ 0. Hence, (ππ + ππ, ππ), (ππ, ππ) ∈ π. Now we need to show that addition and multiplication are well-defined. So we must show that if different representatives in π are chosen, the same element of πΉ will result. Suppose that (π1 , π1 ) ∈ [(π, π)] and (π1 , π1 ) ∈ [(π, π)] . We must show that (π1 π1 + π1 π1 , π1 π1 ) ∈ [(ππ + ππ, ππ)] and (π1 π1 , π1 π1 ) ∈ [(ππ, ππ)] . 5 (π1 , π1 ) ∈ [(π, π)] means that (π1 , π1 )~(π, π) , that is π1 π = π1 π . βΆ (1) Similarly, (π1 , π1 ) ∈ [(π, π)] implies that π1 π = π1 π . βΆ (2) By multiplying (1) by π1 π and (2) by π1 π and adding the resulting equation, we have π1 ππ1 π + π1 ππ1 π = π1 ππ1 π + π1 ππ1 π . Using axioms of π·, we have (π1 π1 + π1 π1 )ππ = π1 π1 (ππ + ππ) , (π1 π1 + π1 π1 , π1 π1 )~(ππ + ππ, ππ) . Thus (π1 π1 + π1 π1 , π1 π1 ) ∈ [(ππ + ππ, ππ)] . Foe multiplication, we multiply (1) and (2). So π1 ππ1 π = π1 ππ1 π , Using axioms of π· we have π1 π1 ππ = π1 π1 ππ . Thus (π1 π1 , π1 π1 )~(ππ, ππ) . Hence (π1 π1 , π1 π1 ) ∈ [(ππ, ππ)] . Step 3: Now we will check the axioms of the field πΉ . 1. Addition in πΉ is commutative. Proof : By definition [(π, π)] + [(π, π)] = [(ππ + ππ, ππ)] and [(π, π)] + [(π, π)] = [(ππ + ππ, ππ)] . We must show that (ππ + ππ, ππ)~(ππ + ππ, ππ) . Using the axioms of π· , we have ππ + ππ = ππ + ππ and ππ = ππ . 2. Addition is associative. 3. [(0, 1)] is an identity element for addition in πΉ. 4. [(−π, π)] is an additive inverse for [(π, π)] in πΉ. 5. Multiplication in πΉ is associative. 6. Multiplication in πΉ is commutative. 6 7. The distributive laws hold in πΉ. 8. [(1, 1)] is a multiplicative identity element in πΉ. 9. If [(π, π)] ∈ πΉ is not the additive identity element, then π ≠ 0 in π· and [(π, π)] is a multiplicative inverse for [(π, π)] . Proof : Let [(π, π)] ∈ πΉ. If π = 0, then π1 = π0 = 0 , So (π, π)~(0, 1) , That is [(π, π)] = [(0, 1)] . But [(0, 1)] is the additive identity by part 3. Thus if [(π, π)] is not the additive identity in πΉ, we have π ≠ 0 . Now [(π, π)][(π, π)] = [(ππ, ππ)] . But in π· we have ππ = ππ , so (ππ)1 = (ππ)1 , and (ππ, ππ)~(1, 1) . Thus [(π, π)][(π, π)] = [(1, 1)] , and [(1, 1)] is the multiplicative identity by part 8. Step 4: We show that πΉ contains π· . Thus, we must show that there is an isomorphism π of π· with a subdomain πΉ. The next lemma gives us this isomorphism. We will inject π· into πΉ. Lemma 4.3: The map π: π· βΆ πΉ given by π(π) = [(π, 1)] is an isomorphism of π· with a subring of πΉ. Proof: Let π, π ∈ π· . Then π(π + π) = [(π + π, 1)] . Also, π(π) + π(π) = [(π, 1)] + [(π, 1)] = [(π1 + 1π, 1)] = [(π + π, 1)] . So, π(π + π) = π(π) + π(π) . Also, π(ππ) = [(ππ, 1)], While π(π)π(π) = [(π, 1)][(π, 1)] = [(ππ, 1)] . So, π(ππ) = π(π)π(π) . Now we show that π is one to one map. If π(π) = π(π) , then [(π, 1)] = [(π, 1)] , so (π, 1)~(π, 1) gives π1 = 1π , that is π = π. Thus π is an isomorphism of π· with π[π·] and π[π·] is a subdomain of πΉ. Theorem 4.4: Any integral domain π· can be enlarge to (or embedded in) a field πΉ such that every element of πΉ can be expressed as a quotient of two elements of . (Such a field πΉ is a field of quotients of π·.) 7 Proof: Since [(π, π)] = [(π, 1)][(1, π)] = [(π, 1)]⁄[(π, 1] = π(π)π(π) which holds in πΉ 8 1.5 Rings of Polynomial: If π is a ring, then π [π₯] is the set of all polynomials with coefficients in the ring π . π₯ in this case is called an indeterminate rather than variable. Definition: Let π be a ring. A polynomial π(π₯) with coefficient in π is an infinite formal sum ∞ ∑ ππ π₯ π = π0 + π1 π₯ + β― + ππ π₯ π + β― π=0 where ππ ∈ π and ππ = 0 for all but a finite number of values of π. The ππ are coefficient of π(π₯). If for some π ≥ 0 it is true that ππ ≠ 0, the largest such value of π is the degree of π(π₯). If all ππ = 0, then the degree of π(π₯) is undefined. Note: * If π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π + β― and π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π + β―, then for polynomial addition, we have π(π₯) + π(π₯) = π1 + π1 π₯ + β― + ππ π₯ π + β― π€βπππ ππ = ππ + ππ , and for polynomial multiplication, we have π π(π₯)π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π + β― π€βπππ ππ = ∑ ππ ππ−π π=0 * ππ and ππ are 0 for all but a finite number of values of π. * If π is not commutative, then π ∑ ππ ππ−π π=0 need not equal 9 π ∑ ππ ππ−π π=0 Theorem 5.1: The set π [π₯] of all polynomials in an indeterminate π₯ with coefficients in a ring π is a ring under polynomial addition and multiplication. If π is commutative, then so is π [π₯], and if π has unity 1 ≠ 0 ,then 1 is also unity for π [π₯]. Example: β€[π₯] is the ring polynomials in π₯ with integral coefficients. β[π₯] is the ring polynomials in π₯ with rational coefficients. Example: Find the sum and the product of the given polynomials in in the given polynomial ring: π(π) = π + π , π(π) = π + π ππ β€π [π]. π(π₯) + π(π₯) = (π₯ + 1) + (π₯ + 1) = 2π₯ + 2 = 0π₯ + 0 = 0. π(π₯)π(π₯) = (π₯ + 1)(π₯ + 1) = π₯ 2 + 2π₯ + 1 = π₯ 2 + 1. π(π) = ππ − π, π(π) = πππ − ππ + π ππ β€π [π]. In β€8 [π₯], we have π(π₯) = 4π₯ + 3 , π(π₯) = 2π₯ 2 + 4π₯ + 2 π(π₯) + π(π₯) = 2π₯ 2 + 8π₯ + 5 = 2π₯ 2 + 0π₯ + 5 = 2π₯ 2 + 5 π(π₯)π(π₯) = 8π₯ 3 + 16π₯ 2 + 8π₯ + 6π₯ 2 + 12π₯ + 6 = 6π₯ 2 + 4π₯ + 6 * The Evaluation homomorphism: Theorem 5.2: (The Evaluation Homomorphism for Field Theory): Let πΉ be a subfield of a field πΈ, let πΌ be any element of πΈ, and let π₯ be an indeterminate. The map ππΌ : π[π₯] βΆ πΈ defined by ππΌ (π0 + π1 π₯ + β― + ππ π₯ π ) = π0 + π1 πΌ + β― + ππ πΌ π 10 for π0 + π1 π₯ + β― + ππ π₯ π ) ∈ πΉ[π₯] is a homomorphism of πΉ[π₯] into πΈ. Also, ππΌ (π₯) = πΌ, and ππΌ maps πΉ isomorphically by the identity map, that is, ππΌ (π) = π for π ∈ πΉ. The homomorphism ππΌ is evaluation at πΌ. Proof: Insertion or deletion of terms 0π₯ π does not affect the value of ππΌ (π(π₯)). If π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π , π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π , πππ β(π₯) = π(π₯) + π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π , then ππΌ (π(π₯) + π(π₯)) = ππΌ (β(π₯)) = π0 + π1 πΌ + β― + ππ πΌ π , and ππΌ (π(π₯)) + ππΌ (π(π₯)) = (π0 + π1 πΌ + β― + ππ πΌ π ) + (π0 + π1 πΌ + β― + ππ πΌ π ). By definition of polynomial addition, we have ππ = ππ + ππ . Hence, ππΌ (π(π₯) + π(π₯)) = ππΌ (π(π₯)) + ππΌ (π(π₯)) . For multiplication, we have π(π₯)π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π . So ππΌ (π(π₯)π(π₯)) = π0 + π1 πΌ + β― + ππ πΌ π , Also, [ππΌ (π(π₯))][ππΌ (π(π₯))] = (π0 + π1 πΌ + β― + ππ πΌ π )(π0 + π1 πΌ + β― + ππ πΌ π ). By definition of polynomial multiplication, we have π ππ = ∑ ππ ππ−π π=0 Thus, ππΌ (π(π₯)π(π₯)) = [ππΌ (π(π₯))][ππΌ (π(π₯))]. Hence ππΌ is a homomorphism. By the definition of ππΌ applied to a constant polynomial π ∈ πΉ[π₯], where π ∈ πΉ, ππΌ (π) = π. Thus, ππΌ maps πΉ isomorphically by the identity map. Again by definition of ππΌ , we have ππΌ (π₯) = ππΌ (1π₯) = 1πΌ = πΌ. Example: Let π = β, πππ π¬ = β. Compute for the indicated evaluation ππ . 11 π0 : β[π₯] βΆ β. π0 (π0 + π1 π₯ + β― + ππ π₯ π ) = π0 + π1 0 + β― + ππ 0π = π0 . Thus, every polynomial is mapped onto its constant term. Example: Let π = β, πππ π¬ = β. Compute for the indicated evaluation ππ (ππ + π − π). π2 : β[π₯] βΆ β. π2 (π0 + π1 π₯ + β― + ππ π₯ π ) = π0 + π1 2 + β― + ππ 2π . π2 (π₯ 2 + π₯ − 6) = 22 + 2 − 6 = 0 . Thus, π₯ 2 + π₯ − 6 is in the kernel π of π2 . Also, π₯ 2 + π₯ − 6 = (π₯ − 2)(π₯ + 3) because π2 (π₯ 2 + π₯ − 6) = 0 is that π2 (π₯ − 2) = 2 − 2 = 0. Example: Let π = β, πππ π¬ = β. Compute for the indicated evaluation ππ (ππ + π). ππ : β[π₯] βΆ β ππ (π0 + π1 π₯ + β― + ππ π₯ π ) = π0 + π1 π + β― + ππ π π πππ ππ (π₯) = π. ππ (π₯ 2 + 1) = π 2 + 1 = 0. So π₯ 2 + 1 is in the kernel π of ππ . Definition: Let πΉ be a subfield of a field πΈ, and let πΌ be an element of πΈ. Let π(π₯) = π0 + π1 π₯ + β― + ππ π₯ π be in πΉ[π₯] and let ππΌ : πΉ[π₯] βΆ πΈ be the evaluation homomorphism of Theorem 5.2. Let π(πΌ) denote ππΌ (π(π₯)) = π0 + π1 πΌ + β― + ππ πΌ π . If π(πΌ) = 0, then πΌ is a zero of π(π₯). Example: Find all real numbers π such that ππ + π − π = π. Let πΉ = β and πΈ = β, we need to find all πΌ ∈ β such that ππΌ (π₯ 2 + π₯ − 6) = 0, 12 that is, finding all zeros of π₯ 2 + π₯ − 6 in β. {πΌ ∈ β | ππΌ (π₯ 2 + π₯ − 6) = 0} = {π ∈ β | π 2 + π − 6 = 0} = {2, −3}. Theorem 5.3: The polynomial π₯ 2 − 2 has no zeros in the rational numbers. Thus √2 is not a rational number. Proof: Suppose that π⁄π for π, π ∈ β€ is a rational number such that (π⁄π)2 = 2. Let the fraction π⁄π be in the lowest terms with gcd(π⁄π) = 1. Then π2 = 2π2 , where both π2 and 2π2 are integers. Since 2 is a factor of 2π2 , 2 must be one of the factors of π2 . But as a square, π2 has as factors of π repeated twice. Thus π2 must have two factors 2. Hence, 2π2 must have two factors 2, so π2 must have 2 as factor, and consequently π has 2 as a factor. Thus π and π must be divisible by 2 which is contradicts that gcd(π, π) = 1. So 2 ≠ (π⁄π)2 for any π, π ∈ β€. 13 1.6 Factorization of Polynomials Over a Field: Let πΈ and πΉ be fields, with πΉ ≤ πΈ. Suppose that π(π₯) ∈ πΉ[π₯] factors in πΉ[π₯], so that π(π₯) = π(π₯)β(π₯) ∈ πΉ[π₯] and let πΌ ∈ πΈ. Now for the evaluation homomorphism ππΌ , we have π(πΌ) = ππΌ (π(π₯)) = ππΌ (π(π₯)β(π₯)) = ππΌ (π(π₯))ππΌ (β(π₯)) = π(πΌ)β(πΌ). Thus, if πΌ ∈ πΈ, then π(πΌ) = 0 if and only if either π(πΌ) = 0 ππ β(πΌ) = 0. *The Division Algorithm in F[x]: Theorem 6.1 (Division algorithm for F[x]): Let π(π₯) = ππ π₯ π + ππ−1 π₯ π−1 + β― + π0 and π(π₯) = ππ π₯ π + ππ−1 π₯ π−1 + β― + π0 be two elements of πΉ[π₯], with ππ and ππ both nonzero elements of πΉ and π > 0. Then there are unique polynomials π(π₯) and π(π₯) in πΉ[π₯] such that π(π₯) = π(π₯)π(π₯) + π(π₯), where either π(π₯) = 0 or the degree of π(π₯) is less than the degree π of π(π₯). Example: Find π(π) and π(π) as described by the division algorithm theorem. π(π) = ππ − πππ + πππ + ππ − π , 14 π(π) = ππ − ππ + π ππ β€π [π]. Corollary 6.2: (Factor Theorem): An element π ∈ πΉ is a zero of π(π₯) ∈ πΉ[π₯] if and only if π₯ − π is a factor of π(π₯) in πΉ[π₯]. Proof: Suppose that for π ∈ πΉ we have π(π) = 0. By Theorem 6.1. there exist π(π₯), π(π₯) ∈ πΉ[π₯] such that π(π₯) = (π₯ − π)π(π₯) + π . Applying the evaluation homomorphism, ππΌ : πΉ[π₯] βΆ πΉ of Theorem 5.2, we find 0 = π(π) = 0π(π) + π, so it must be that π = 0. Then π(π₯) = (π₯ − π)π(π₯), so π₯ − π is a factor of π(π₯). Conversely, if π₯ − π is a factor of π(π₯) in πΉ[π₯], where π ∈ πΉ, then applying the evaluation homomorphism ππΌ to π(π₯) = (π₯ − π)π(π₯), we have π(π) = 0π(π) = 0. Example: The polynomial (ππ + πππ + ππ + π) can be factored into linear factors in β€π [π]. Find this factorization. 15 16 Corollary 6.3: A nonzero polynomial π(π₯) ∈ πΉ[π₯] of degree π can have at most π zeros in a field πΉ. Proof: If π1 ∈ πΉ is a zero of π(π₯), then π(π₯) = (π₯ − π1 )π1 (π₯), where the degree of π1 (π₯) is π − 1. A zero π2 ∈ πΉ of π1 (π₯) then result in a factorization π(π₯) = (π₯ − π1 )(π₯ − π2 )π2 (π₯). Continuing this process, we have π(π₯) = (π₯ − π1 ) … (π₯ − ππ )ππ (π₯), where ππ (π₯) has no further zeros in πΉ. Since the degree of π(π₯) is π, at most π factors (π₯ − ππ ) can appear on the right-hand side of the preceding equation, so π ≤ π. Also, if π ≠ ππ for π = 1, … , π and π ∈ πΉ, then π(π) = (π − π1 ) … (π − ππ )ππ (π) ≠ 0, since πΉ has no divisors of 0 and none of π − ππ or ππ (π) are 0 by construction. Hence, the ππ for π = 1, . . , π ≤ π are all the zeros in πΉ of π(π₯). Corollary 6.4: The multiplicative group of all nonzero elements of a finite field is cyclic. * Irreducible Polynomials: Definition: A nonconstant polynomial π(π₯) ∈ πΉ[π₯] is irreducible over πΉ or is an irreducible polynomial in πΉ[π₯] if π(π₯) cannot be expressed as a product π(π₯)β(π₯) of two polynomials π(π₯) 17 18